MULTIMOD Mark II : A Revised and Extended Model: Occa Paper No.71. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1990)
This paper explains different features of the MULTI-region econometric MODel (MULTIMOD). MULTIMOD is designed to examine the effects on that baseline of scenarios that involve changes in policies in major countries and other exogenous changes in the economic environment. The Mark II version described in this paper disaggregates the larger industrial bloc into its component countries, and, as a result, comprises eight industrial countries/regions and two developing country regions. In addition, some of the equations have been re-specified and re-estimated. The capital exporting countries, primarily high-income oil exporters, are treated separately in simplified form: they are the residual suppliers of oil, whose price is exogenous in real terms, and their exports of other goods are exogenous. The model, because it includes expectations that are consistent with its solution values in later periods, is well suited to evaluate the effects of policies that are announced and credible.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet